Targeting BAFF and APRIL in systemic lupus erythematosus and other antibody-associated diseases. (2nd January 2017) - Samy, Eileen; Wax, Stephen; Huard, Bertrand; Hess, Henry; Schneider, Pascal
ABSTRACT: The B cell-stimulating molecules, BAFF (B cell activating factor) and APRIL (a proliferation-inducing ligand), are critical factors in the maintenance of the B cell pool and humoral immunity. In addition, BAFF and APRIL are involved in the pathogenesis of a number of human autoimmune diseases, with elevated levels of these cytokines detected in the sera of patients with systemic lupus erythematosus (SLE), IgA nephropathy, Sjögren's syndrome, and rheumatoid arthritis. As such, both molecules are rational targets for new therapies in B cell-driven autoimmune diseases, and several inhibitors of BAFF or BAFF and APRIL together have been investigated in clinical trials. These include the BAFF/APRIL dual inhibitor, atacicept, and the BAFF inhibitor, belimumab, which is approved as an add-on therapy for patients with active SLE. Post hoc analyses of these trials indicate that baseline serum levels of BAFF and BAFF/APRIL correlate with treatment response to belimumab and atacicept, respectively, suggesting a role for the two molecules as predictive biomarkers. It will, however, be important to refine future testing to identify active forms of BAFF and APRIL in the circulation, as well as to distinguish between homotrimer and heteromer configurations. In this review, we discuss the rationale for dual BAFF/APRIL inhibition versus single BAFF inhibition in autoimmune disease, by focusing on the similarities and differences between the physiological and pathogenic roles of the two molecules. A summary of the preclinical and clinical data currently available is also presented.